Analisis Wacana Kritis Model Norman Fairclough Pada Pemberitaan Aksi Penusukan Kemenpolhukam di IDN TIMES - Sumartono Sumartono; Yosi Aprilia Yonanda; Hani Astuti (Prisani Cendekia Institute, 2022)
News is not only an information about events, and/or opinions, but also a discourse and ideology of mass media management to the public. Various information that was broadcast by the mass media, one of which was the news of the stabbing of Kemenpolhukam Wiranto in October 2019 at IDN TIMES. Through Norman Fairclough's critical discourse analysis, the researcher will analyze how IDN TIMES discusses the news of the stabbing of Wiranto which will form a certain ideology for its readers. The results of the study show that news is not only information for readers, but also a place for forming ideology by the media.